Controlling Parameters of Benthic Deep-Sea Foraminiferal Biogeography at the Brazilian Continental Margin (11-22°S) - Saupe, Anna; Schmidt, Johanna; Petersen, Jassin; Bahr, André; Dias, Bruna Borba; Albuquerque, Ana Luiza Spadano; Díaz Ramos, Rut Amelia; Grunert, Patrick (Frontiers in Marine Science, 2022)
This study presents new quantitative data on benthic foraminifera from three bathymetric transects of the Brazil (11-14°S, 420-1900 m) and Campos (22°S, 430-2000 m) basins. The quantity and quality of organic matter flux as well as substrate properties and hydrodynamic conditions at the sediment-water interface are identified as key parameters controlling assemblage distribution. Based on the total (stained and unstained) fauna, a distinct biogeographic divide between a Globocassidulina subglobosa/crassa assemblage in the Campos Basin and a rosalinid/bolivinid assemblage in the Brazil Basin occurs across the bifurcation of the South Atlantic Central Water into its southward subtropical and northward tropical branches. In the Campos Basin, coarser sediments, increased bottom current activity, and variable nutrient supply favor an assemblage of Globocassidulina subglobosa/crassa, Nuttalides umbonifer and Alabaminella weddellensis. Occurrences of cold-water coral mounds in 870 m provide an ecological niche favoring species such as Alabaminella weddellensis which benefit from trapped nutrients. The Brazil Basin is characterized by increased abundances of Rosalina and Bolivina, while Globocassidulina subglobosa/crassa is comparatively less frequent. Assemblages with G. subglobosa/crassa, Rosalina spp., Bolivina variabilis and Bolivina subreticulata are favored by a relatively high nutrient input at 14°S. Further north, assemblages with Bolivina subreticulata, Bolivina variabilis, Epistominella exigua, G. subglobosa/crassa are located beneath the velocity core of the North Brazil Undercurrent (NBUC), coinciding with more clayey sediments rich in TOC. Occurrences of delicate branching forms such as Saccorhiza ramosa indicate a more stable setting, distal to the main current. Rose Bengal stained (living) specimens are scarce in all three regions, as is typical for deep-sea foraminiferal faunas. Their patterns of species distribution largely reflect those observed for the total fauna.